Low energy availability in females: Risk, knowledge, and education - Pai, N.N. (University of Otago, 2023)
This dissertation consists of three major studies: Study I Background: Assessing knowledge on the signs and symptoms of Relative Energy Deficiency in Sport (RED-S) among athletes and healthcare professionals can aid in developing targeted education and training for the sports medicine team. However, there is no consensus on a valid tool for evaluating RED-S knowledge. Aim: The aim of this study was to develop and validate a questionnaire which assesses knowledge on signs and symptoms of RED-S among healthcare professionals and physically active individuals. Methods: The questionnaire was created in two phases: item development and item validation. Item development was established through literature review, expert review (n=4) and pre-testing (n=35). Item validation was demonstrated by administrating the developed questionnaire among healthcare professionals (n=97) and physically active individuals (n=77) for item analysis, internal reliability, and construct validity. The questionnaire was re- administered in the same groups (n=88) for test-retest reliability. Results: The final questionnaire has 18 items. The expert responses showed >80% acceptability, and good content and face validity. Item response analysis resulted in removal of six items due to low discrimination ability. Construct validity was confirmed with significantly higher knowledge scores in healthcare professionals compared with non-health professionals (mean difference (95% CI) = 2.8 (1.9, 3.7)). Internal consistency, assessed using Cronbach`s alpha (? =0.79), and test-retest reliability using intra-class correlation coefficients (ICC=0.80; Spearman`s correlation = 0.84, p<0.001), were good. Conclusion: This questionnaire provides a valid and reliable tool to assess knowledge on signs and symptoms of RED-S among female healthcare professionals and physically active individuals. This information will provide valuable data to develop targeted education material. Study II Background: Nutrition knowledge is potentially both a barrier to and a facilitator of adequate dietary intakes amongst athletes. Inadequate dietary intakes can result in Low Energy Availability (LEA) which can lead to serious health outcomes - a cascade is known as RED-S. To date, there is very little information on the relationship between nutrition knowledge and risk of LEA amongst female team sport athletes. Aim: This study aims to determine whether general and sports nutrition knowledge is associated with the risk of LEA amongst female team sport athletes. Methods: Using a cross-sectional study design, female athletes (>16 years old) who participated in team sports in New Zealand completed an online questionnaire. The questionnaire included the LEA in Female Questionnaire (LEAF-Q) to determine LEA risk, and the Abridged Sport Nutrition Knowledge Questionnaire (ANSK-Q) to assess general nutrition, and sports nutrition knowledge. The relationship between LEA risk and knowledge, as well as other factors like age and BMI, was analysed using the Kruskal-Wallis test of independent variables and Chi-square tests. Results: Among the 100 female athletes (mean (±sd) age: 21.9 (± 6.09) years; BMI: 25.1 kg/m2 (±3.29) who completed the questionnaire, 53% were at-risk for LEA, and 70% (n=67) had poor general and sports nutrition knowledge. Female athletes who were `at-risk` for LEA and those who were `not at-risk` for LEA did not differ statistically in terms of age (p=0.350) or BMI (p=0.576). 54% of the participants who were `not at risk` for LEA had an A-NSK score between 50 and 60% (i.e., average knowledge), whereas 54% of the athletes who were `at risk` for LEA had poor nutrition knowledge. However, there was no statistical difference between the groups (p=0.273). Conclusion: More than half of the athletes were `at-risk` for LEA, which is similar to the prevalence rates amongst other athletic populations in New Zealand. The knowledge scores of the athletes who were `at risk` of LEA and those who were `not at risk` of LEA were not statistically significantly or practically different. Additionally, the overall findings of poor nutrition knowledge among team sports athletes implies the need for nutrition education. Study III Background: Social media platforms such as Instagram have the potential to reach a large audience and may be well-suited for promoting RED-S related education. Thus, it is timely to consider Instagram's role in education and awareness, with a special focus on RED- S knowledge and awareness, including its benefits and limitations. Aim: The aim of pilot study was to assess the reliability, accuracy, clarity, and level of engagement of existing Instagram posts on the definition of RED-S. Methods: We systematically searched for publicly available Instagram accounts that provided information on RED-S related photos, infographics, and videos over a 3-week period using three hashtags: #relativeenergydeficiencyinsports, #relativeenergydeficiency and #lowenergyavailability. The post URL, caption text, the account holder's qualification, the image posted, the number of followers and likes, and the hashtags for the post were recorded for each post. Posts not in English, relating to food, eating disorders, and mental health were excluded. Two experts evaluated the quality of the content based on four criteria: accuracy (`not accurate` (=1) to `extremely accurate (=5)), clarity (`not clear` (=1) to `extremely clear` (=5)), understandability (`not easy to understand` (=1) to `extremely easy to understand (=5)) and engagement (`not engaging`(=1) to `extremely engaging (=5)). The like-to-follower ratio, which reflects the percentage of followers who react by "liking" the post was calculated. The Kruskal-Wallis rank test was used to compare the number of likes, followers, and total quality score for posts with infographics or written content images. The association between total quality score, likes, followers, and like-to-follower ratio were examined using Spearman's rank correlation test. Results: 4,632 posts with RED-S related hashtags were identified, of these 34 RED-S definitions-related posts were eligible and used for final review. The posts had a median of 29 likes (25th/ 75th percentile:11, 137) and a median of 1,714 followers (25th/ 75th percentile: 454, 10,800). Based on expert review, 52% (n=18) were rated high for accuracy, 58%(n=20) for clarity, 50%(n=17) for level of understanding, and 36% (n=12) for level of engagement. Based on their Instagram profile 80% of account holders had formal academic or professional qualifications, with 30% being identified as dietitians and nutritionists. Total quality score of each post ranged from 7-16 (out of 20) with a mean (SD) of 13.3. (4.1); non-profit organizations received the highest mean score (16). There were no statistically significant differences between the number of likes, followers, and total quality score received by the two types of posts (i.e., posts with and without infographics) (all p>0.05). The like-to-follower ratio was non-significantly negatively correlated with the total quality score of Instagram posts (i.e., accuracy, clarity, understanding, and interesting) (rs=-0.216, p=0.220). Conclusion: Our findings suggest that physically active people and athletes should be encouraged to follow specific Instagram accounts such as IOC and Athlete Triad Coalition to obtain accurate (i.e., evidence-based information which was simple to understand) and clear information on the definition of RED-S. Overall, among 48% of the posts shared by account holders with a professional qualification, 12% (n=4) contained inaccurate or misleading information, and 36% (n=14) provided an incomplete picture of the definition of RED-S reflecting that there is limited understanding on RED-S condition.